Treasury Stock Sales and Management Rights Protection: Conflicts of Interest between an Owner-manager and Small Shareholders - Sung Ick Cho (KDI Journal of Economic Policy, 2017)
This paper investigates the sales process of treasury stocks, while most previous research studies treasury stock repurchases. The sales of treasury stocks are an important measure to protect management rights only in Korea, as Korea's laws and systems allow treasury stock sales according to the board's resolution and not by the decisions made at the general shareholders' meetings. The board's resolution, which considers the owner-manager's interest on management rights, can cause damages to small shareholders. Considering (i) the economic characteristics of treasury stocks, (ii) other countries' institutions and experiences, (iii) a theoretical assessment of the possibility of small shareholder losses, and (iv) lessons from Korea's actual instances, Korea's present system should be corrected at least in the mid and long term. Even in the short-term, rules pertaining to sales enacted by the board's resolution inducing small shareholder losses should be overhauled. The autonomous discipline by various stakeholders could be an ideal measure by which to monitor ownermanager's decisions. In addition, temporary intervention measures, such as government examinations, could be implemented to protect small shareholders.
Keywords: K22; G34; G38; 330; Treasury Stock; Management Right; Corporate Governance